Demographical and Clinical Characteristic of Urolithiasis Inpatient in Buleleng District General Hospital on 2021 - I Gde Arie Kusuma Wijaya; Made Suadnyani Pasek; I Gede Surya Dinata (WMJ (Warmadewa Medical Journal), 2024)
Urolithiasis is the most common emergency condition in urology and is often diagnosed in urology centers. It is important to know the epidemiology of urolithiasis to help improve medical services for urolithiasis patients. Urolithiasis prevalence has increased in the world. Bali Province occupies the fourth rank with a prevalence of kidney stones of 0.7%, and Buleleng Regency is included in the top five cases of urolithiasis in Bali with a 0.9% prevalence. Unfortunately, data in Buleleng Regency has not been tabulated in detail in terms of demographic and clinical characteristics. The purpose of this research was to observe and analyze the demographic and clinical characteristics of inpatients with urinary tract stones at Buleleng District Hospital in 2021. This research is a descriptive cross-sectional study using secondary medical record data with a total sampling method. The data were analyzed using descriptive statistics. Of the 45 samples, the dominant result in the age group of 15-64 years was 86.7%, male (75.6%), employee occupation group (64.4%), and Buleleng district (31.1%). The dominant clinical symptoms are back pain (82.2%), nephrolithiasis (68.8%), size > 20 mm (93.3%), enforced by BOF (86.7%), urinalysis (95.6%), managed by URS flexible lithotripsy (73.3%), urinary tract infection as a complication (53.3%), and no comorbidities (80.1%). Most of the urolithiasis patients are male office workers in the productive age group, predominating in Buleleng District, and managed with URS flexible lithotripsy with predominant complications of UTI (urinary tract infection) and no comorbidities.